Номінації прибережно-водної рослинності в західнополіських говірках - Омельковець, Руслана Степанівна; Черевко, Марія Василівна; Omelkovets, Ruslana S.; Cherevko, Mariia V. (My University, 2017)
У статті на підставі самостійно зібраних за розробленою програмою матеріалів представлено чималий набір номенів, які репрезентують болотні рослини в західнополіських говірках, визначено специфіку номінації цієї лексико-тематичної групи.

Introduction. The article is based on independently developed program and collected sources which present considerable empirical material – set of noments representing coastal-aquatic vegetation in westernpollisyan dialects, identified specific category of lexical and thematic groups. Main text. Names of coastal-aquatic vegetation in westernpollisyan dialects form a plentiful vocabulary in terms of thematic group, level of representation and nominative variability of desyhnativs which are different. Lexical variation of group thoroughly imbued by synonymous relations, besides the same names for nomination of several desyhnativs are used. Summary and Conclusions. Most types of coastal-aquatic vegetation – monolexems. Analytical names are represented mainly by the type of attributive phrases.
Nominatives in the coastal-aquatic vegetation lexis in the westernpollisyan dialects
Keywords: номінація; лексема; засоби номінації; прибережно-водна рослинність; nomination; lexem; tools of formation of titles; coastal-aquatic vegetation; westernpollisyan dialect